PERSEPSI MAHASISWA UNIVERSITAS RIAU TERHADAP KEPEMIMPINAN CALON PRESIDEN REPUBLIK INDONESIA PERIODE 2019-2024 - Toedien, Fahmi Amri; Erlinda, Sri; Arianto, Jumili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Public perception is very important in the sustainability of a leadership, so that leaders can assess what must be done in carrying out their leadership. Students referred to as intellectuals are considered critical of the political conditions in Indonesia, of course, having a deep perception of the two pairs of presidential candidates at this time, bearing in mind that both pairs of candidates have different character and background that will hold the highest authority in the country. This research is structured with the formulation of the problem